STRUGGLING WITH INTERNATIONAL TRAFFIC DRUGS - MUSAEV, Djamaliddin (Journal of Fundamental Studies, 2023)
The article is devoted to the search for political instruments to counter the international drug business. The importance of the leading role of the UN, interregional organizations to combat drug trafficking, and international cooperation programs to prevent drug trafficking was noted. Also, the article deals with the problem of the spread of drug addiction among some of the youth, as well as the fight against drug addiction, and the positions of the current issue in the country are considered. The experience of foreign countries in this area, especially the prevention and prevention of drug addiction among individuals of the population, is considered. Measures are proposed that may possibly limit this antisocial phenomenon.